Factors that affect Fraudulent Financial Reporting - Kharissa Setiawan; Ita Trisnawati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The objective of this research is to obtain empirical evidence of the influence of factors that can affect fraudulent financial reporting. Those factors are financial targets, financial stability, external pressure, institutional ownership, number of audit committee members, ineffective monitoring, nature of industry, external auditor quality, the change of auditor, auditor’s opinion, change of directors, proportion of independent commissioner, and numbers of CEO’s picture. The variables used on this research if from fraud pentagon theory perspective. This research’s population is manufacturing companies listed in Indonesia Stock Exchange (IDX) from 2017 to 2020. The sample of this research is selected by using purposive sampling based on several criteria. This research uses 302 data from 101 listed manufacturing companies as the sample. The method used for analyzing and testing the data on this research is by multiple regression to see the influence between independent variables and fraudulent financial reporting. The result of this research shows that financial targets, nature of industry, and auditor’s opinion have significant influence on fraudulent financial reporting. In contrast, financial stability, external pressure, institutional ownership, number of audit committee members, ineffective monitoring, external auditor quality, the change of auditor, change of directors, proportion of independent commissioner, and numbers of CEO’s picture have no significant value to fraudulent financial reporting.